Factors of changes in farming in Piła subregion in the view of Agricultural Censuses in 1996, 2002 and 2010 = Czynniki zmian w rolnictwie i na obszarach wiejskich w podregionie pilskim w świetle Powszechnych Spisów Rolnych z lat 1996, 2002 i 2010 - Czyżewski, Andrzej; Strońska-Ziemann, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The conducted factor analysis, basing on the outcomes of three successive Agricultural Censuses, selected four factors of changes in agriculture and rural areas of Pila subregion and determined the variation range they accounted for. They were induced by natural environment conditions, production limits of agricultural holdings, the level of entrepreneurship, labour market situation. Those variables, in turn, contributed to the suburbanisation processes and road network and social infrastructure development, as well as their derivatives, such as, the level of incomes, advances in construction industry and the level of pre-schooling. Agriculture contributed negatively (destimuli) to region?s development in analysed years.
Keywords: rolnictwo; obszary wiejskie; determinanty zmian; analiza czynnikowa; podregion pilski; agriculture; rural areas; determinants of changes; factor analysis; Pila subregion